PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PENERAPAN METODE MULTISENSORI BERBASIS DIRECT INSTRUCTION SISWA KELAS III DI SD DENGAN KESULITAN BELAJAR - Faridah; Rendy Roos Handoyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The low level of beginning reading skills among students with learning difficulties is influenced by the continued use of conventional teaching methods that do not adequately accommodate their learning characteristics. This study aimed to improve beginning reading skills through the implementation of a multisensory method based on Direct Instruction. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted over two cycles. The participants were two third-grade elementary school students who experienced difficulties in beginning reading. Data were collected through beginning reading tests, student participation observations, and classroom learning observations. The data were analyzed using descriptive qualitative and quantitative techniques, with a success criterion of 80%. The findings indicated that the beginning reading skills of both participants improved across each cycle. In the pre-action stage, their reading skills were still in the low category. Following the implementation of the Direct Instruction-based multisensory method in Cycle I, their beginning reading skills improved but had not yet reached the predetermined success criterion. In Cycle II, both students demonstrated further improvement and successfully achieved the targeted level of performance. In addition, students' participation during the learning process also increased. These findings indicate that the implementation of a multisensory method based on Direct Instruction was able to improve the beginning reading skills of students with learning difficulties. ABSTRAK Rendahnya kemampuan membaca permulaan pada siswa yang mengalami kesulitan belajar dipengaruhi oleh pembelajaran yang masih didominasi metode konvensional sehingga belum mengakomodasi karakteristik belajar siswa secara optimal. Penelitian ini bertujuan meningkatkan kemampuan membaca permulaan siswa melalui penerapan metode multisensori berbasis Direct Instruction. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus dengan mengadopsi model Kemmis dan McTaggart. Subjek penelitian terdiri atas dua siswa kelas III SD yang mengalami kesulitan membaca permulaan. Data dikumpulkan melalui tes kemampuan membaca permulaan, observasi partisipasi siswa, dan observasi keterlaksanaan pembelajaran. Data dianalisis secara deskriptif kualitatif dan kuantitatif dengan indikator keberhasilan sebesar 80%. Hasil penelitian menunjukkan bahwa kemampuan membaca permulaan kedua subjek mengalami peningkatan pada setiap siklus. Pada kondisi pra tindakan, kemampuan membaca masih berada pada kategori rendah. Setelah penerapan metode multisensori berbasis Direct Instruction pada Siklus I, kemampuan membaca permulaan meningkat, namun belum mencapai indikator keberhasilan. Pada Siklus II, kemampuan membaca kedua subjek kembali meningkat hingga mencapai indikator keberhasilan yang telah ditetapkan. Selain itu, partisipasi siswa selama proses pembelajaran juga menunjukkan peningkatan. Dengan demikian, penerapan metode multisensori berbasis Direct Instruction mampu meningkatkan kemampuan membaca permulaan siswa yang mengalami kesulitan belajar.